2021
DOI: 10.1038/s41422-021-00563-0
|View full text |Cite
|
Sign up to set email alerts
|

A new type of ERGIC–ERES membrane contact mediated by TMED9 and SEC12 is required for autophagosome biogenesis

Abstract: Under stress, the endomembrane system undergoes reorganization to support autophagosome biogenesis, which is a central step in autophagy. How the endomembrane system remodels has been poorly understood. Here we identify a new type of membrane contact formed between the ER-Golgi intermediate compartment (ERGIC) and the ER-exit site (ERES) in the ER-Golgi system, which is essential for promoting autophagosome biogenesis induced by different stress stimuli. The ERGIC-ERES contact is established by the interaction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 97 publications
1
31
0
1
Order By: Relevance
“…A study found that the cell biological mechanism of misfolded protein cargo entrapment was related to the targeting of TMED9 to the small molecule BRD4780 ( Dvela-Levitt et al, 2019 ). In addition, membrane contact between the ER—Golgi intermediate compartment (ERGIC) and the ER-exit site (ERES) mediated by TMED9 constituted the occurrence of autophagosomes ( Li et al, 2021 ). The transmembrane protein TMED10 was recently identified as a protein channel mediating vesicle translocation and secretion of termed cytosolic leaderless proteins (cytosolic proteins lacking a signal peptide) ( Nguyen and Debnath, 2020 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study found that the cell biological mechanism of misfolded protein cargo entrapment was related to the targeting of TMED9 to the small molecule BRD4780 ( Dvela-Levitt et al, 2019 ). In addition, membrane contact between the ER—Golgi intermediate compartment (ERGIC) and the ER-exit site (ERES) mediated by TMED9 constituted the occurrence of autophagosomes ( Li et al, 2021 ). The transmembrane protein TMED10 was recently identified as a protein channel mediating vesicle translocation and secretion of termed cytosolic leaderless proteins (cytosolic proteins lacking a signal peptide) ( Nguyen and Debnath, 2020 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, a role of TFG in ER-associated autophagy was proposed, further supporting potential involvement of TFG in the crosstalk of the endolysosomal system and ER (Carinci et al, 2021). However, another study suggested that ERES-ER-GIC-associated autophagy does not require TFG (Li et al, 2021). We speculate that the TFG function in the endosomal system, possibly promoting sorting to lysosomal degradation pathway, may be similar to the proposed role of TFG in COPII vesicle uncoating and spatially organizing the ERES-ER-GIC trafficking ''hub.''…”
Section: Tfg Knockdown Regulates Endosomal Sorting Of Egf:egfr Comple...mentioning
confidence: 97%
“…It has long been known that TMED9 participates in ER exit site (ERES) formation for cargo transport to the Golgi (Lavoie et al, 1999;Fujita et al, 2011). However, Li et al (2022) found that ERES-localized Sec12 and ERGIC-localized TMED9 interact directly in trans through their cytoplasmic domains, bringing ERES into close proximity with the ERGIC. ERES-ERGIC association is important for the generation of starvation-induced autophagosomes (Li et al, 2022).…”
Section: Tmed9 In Autophagymentioning
confidence: 99%